The Good Merger - Dafny, Leemore S; Lee, Thomas H (The New England journal of medicine, 2015)
A good health care merger increases the value of care by reducing costs, improving outcomes, or both, enabling providers to generate and respond to competition. Such mergers generate “cognizable efficiencies” offsetting the potential harm of increased prices. The U.S. health care sector relies on private markets to satisfy patient needs as fully and efficiently as possible. To realize this objective, it seems clear that providers must jettison the strategies of old — such as maximizing output within each narrow service line — and embrace new approaches — such as building teams around patient needs rather than around clinicians and facilities. 1 Forward-looking providers are beginning to measure and report condition-specific outcomes and to negotiate bundled-payment contracts that reward care redesign. As providers work to bring value-driven marketplaces to life, many are searching for allies. Their boards and the . . .